A DNA Vaccine Encoding Plasmodium falciparum PfRH5 in Cationic Liposomes for Dermal Tattooing Immunization - Wesley Luzetti Fotoran; Nicole Kleiber; Christiane Glitz; Gerhard Wunderlich (Vaccines, 2020)
Vaccines are the primary means of controlling and preventing pandemics and outbreaks of pathogens such as bacteria, viruses, and parasites. However, a major drawback of naked DNA-based vaccines is their low immunogenicity and the amount of plasmid DNA necessary to elicit a response. Nano-sized liposomes can overcome this limitation, enhancing both nucleic acid stability and targeting to cells after administration. We tested two different DNA vaccines in cationic liposomes to improve the immunogenic properties. For this, we cloned the coding sequences of the Plasmodium falciparum reticulocyte binding protein homologue 5 (PfRH5) either alone or fused with small the small hepatitis virus (HBV) envelope antigen (HBsAg) encoding sequences, potentially resulting in HBsAg particles displaying PfRH5 on their outside. Instead of invasive intraperitoneal or intramuscular immunization, we employed intradermal immunization by tattooing nano-encapsulated DNA. Mice were immunized with 10 μg encapsulated DNA encoding PfRH5 alone or in fusion with HBsAg and this elicited antibodies against schizont extracts (titer of 104). Importantly, only IgG from animals immunized with PfRH5-HBs demonstrated sustained IgG-mediated inhibition in in vitro growth assays showing 58% and 39% blocking activity after 24 and 48 h, respectively. Intradermal tattoo-vaccination of encapsulated PfRH5-HBsAg coding plasmid DNA is effective and superior compared with an unfused PfRH5-DNA vaccine, suggesting that the HBsAg fusion may be advantageous with other vaccine antigens.